Media Pembelajaran: Produktif Boga - Surya Tjahyadi; Hafiz Hamidi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
SMK Negeri 2 Batam is a public school established in 2006, accredited "A", located in the heart of Batam, Jalan Pemuda 5, Legenda Malaka. This public school has five academic programs namely Fashion, Hospitality, Tourism, Fashion and Dining. Each program has been designated as a flagship center of SMKN 2 Batam to develop the highest quality alumni as a center of excellence, Education Unit Revised Curriculum 2013 SMKN 2 Batam No 11002210 has a public school status and is named Nursya Form of vocational secondary education (SMK) led by bani divides and supervises several areas including curriculum, public relations, library, information technology, finance, human resources and administration, facilities and curriculum. The goal is to apply the author's skills learned by the author in the information systems study program, specialization in visual communication design and help the school to facilitate the process of teaching and learning activities.